Productivity and trade growth in services: How services helped power factory Asia - Ben Shepherd (Asian Development Bank Institute (ADBI), 2019)
This paper uses a theory-based measure of productivity-based comparative advantage to examine the trade performance of developing Asian economies in manufacturing and services over the 1995-2011 period. We find that the growth in service exports was nearly as rapid as that in manufacturing over this period - a little-appreciated fact. Services are therefore an integral part of "Factory Asia." Moreover, the results from a quantitative model of trade show that revealed productivity measures are often comparable between manufacturing and services at a disaggregated level, although the results differ markedly across sectors and economies. We also find evidence of rapid growth in revealed productivity in some service subsectors, comparable to that in manufacturing. Our findings suggest that oversimplifying the relationship between patterns of specialization and subsequent economic transformation and growth patterns misses important elements of reality.
Keywords: F14; F15; L80; 330; services; trade; comparative advantage; productivity; Asia